Efficiency and equity aspects of energy taxation - Toon Vandyck (European Regional Science Association (ERSA), 2013)
We analyse the distributional effects of increased oil excises in Belgium by combining a regional Computable General Equilibrium (CGE) model with a microsimulation framework that exploits the rich detail of household-level data. The results suggest that policymakers face an equity-efficiency trade-off driven by the choice of revenue recycling options. Regional impact variation appears to be substantial.
Keywords: 330; energy policy; cge; microsimulation